(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The effectiveness of the method of teaching a foreign language using Bloom’s taxonomy has been proven in linguistics for several years. However, although many have heard of Bloom’s taxonomy, they do not know what kind of program it is and how effective it is in the teaching process. This article discusses the history of the origin of Bloom’s taxonomy, its purpose, its importance in the development and organization of the teaching process, and methods of its application in classroom activities.